Microbial Infection and Antibiotic Susceptibility of Diabetic Foot Ulcer in China: Literature Review - Du, Fang; Ma, Jing; Gong, Hongping; Bista, Raju; Zha, Panpan; Ren, Yan; Gao, Yun; Chen, Dawei; Ran, Xingwu; Wang, Chun (Frontiers in Endocrinology, 2022)
Objective To investigate the microbial spectrum isolated from foot ulcers among diabetic patients in China, which was conducted to help clinicians choose optimal antibiotics empirically. Method The PubMed, MEDLINE, Web of Science, China Biology Medicine (CBM), China National Knowledge Infrastructure (CNKI), WanFang, and VIP databases were searched for studies published between 2015 to 2019, that report primary data on diabetic foot infection (DFI) and antibiotic susceptibility in China. Result A total of 63 articles about DFI and antibiotic susceptibility tests among diabetic patients in China were included. There were 11,483 patients with an average age of 60.2 ± 10.1 years and a mean course of 10.6 ± 5.0 years between 2010 and 2019, covering most geographical regions of China. The prevalence of Gram-positive (GP) bacteria (43.4%) was lower than that of Gram-negative (GN) (52.4%). The most prevalent pathogens isolated were Staphylococcus aureus (17.7%), Escherichia coli (10.9%), Pseudomonas aeruginosa (10.5%), Klebsiella pneumoniae (6.2%), Staphylococcus epidermidis (5.3%), Enterococcus faecalis (4.9%), and fungus (3.7%). The prevalence of polymicrobial infection was 22.8%. GP bacteria were sensitive to linezolid, vancomycin, and teicoplanin. More than 50% of GN bacteria were resistant to third-generation cephalosporins, while the resistance rates of piperacillin/tazobactam, amikacin, meropenem, and imipenem were relatively low. Among the 6017 strains of the isolated organisms, 20% had multi-drug resistance (MDR). Staphylococcus aureus (30.4%) was the most predominant MDR bacteria, followed by extended-spectrum β-lactamase (ESBL) (19.1%). Conclusion The microbial infection of foot ulcers among diabetic patients in China is diverse. The microbial spectrum is different in different geographic regions and Staphylococcus aureus is the predominant bacteria. Polymicrobial and MDR bacterial infections on the foot ulcers are common. This study could be valuable in guiding the empirical use of antibiotics for diabetic foot infections.